Quo Vades Ekonomi Islam? - Muhammad Anzar Manic; Salsabila Putri; Muhammad Zaini El Wahyu (Jurnal Al-fatih Global Mulia, 2024)
Islamic economics is developing as an alternative to the conventional economic system that is often unable to address the challenges of economic inequality and environmental crisis. This article reviews the development of the Islamic economy in Indonesia, identifies key challenges and opportunities, and analyzes the role of government and digital technology in enhancing the inclusiveness of the Islamic economy. Through a literature review, this research finds that regulatory support and the integration of digital innovation can strengthen the sustainability of the Islamic economy in Indonesia. These results emphasize the importance of a maqashid sharia-based approach to create an equitable and sustainable economic system